2015
DOI: 10.1186/s12889-015-2659-4
|View full text |Cite
|
Sign up to set email alerts
|

The correlates of after-school sedentary behavior among children aged 5–18 years: a systematic review

Abstract: BackgroundChildren and adolescents spend a large proportion of the after-school period in sedentary behaviors (SB). Identifying context-specific correlates is important for informing strategies to reduce these behaviors. This paper systematically reviews the correlates of children’s and adolescents’ after-school SB.MethodsA computerized literature search was performed in October 2015 for peer-reviewed original research journal articles published in English before October 2015. Eligibility criteria included: 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 56 publications
2
50
2
3
Order By: Relevance
“…Higher parental educational level also appeared to predict less ST across previous studies [27], and this study confirms this finding; this may be explained by better parental role modelling encouraging schoolchildren to spend less time in front of a screen. Surprisingly, however, this study found that students with higher grades were more likely to meet ST guidelines, a result inconsistent with previous studies [24,35]. This interesting discovery may be interpreted as showing that students with higher grades take on more homework, which thus occupies more of their time, reducing the time available for screen-based activities.…”
Section: Discussioncontrasting
confidence: 99%
“…Higher parental educational level also appeared to predict less ST across previous studies [27], and this study confirms this finding; this may be explained by better parental role modelling encouraging schoolchildren to spend less time in front of a screen. Surprisingly, however, this study found that students with higher grades were more likely to meet ST guidelines, a result inconsistent with previous studies [24,35]. This interesting discovery may be interpreted as showing that students with higher grades take on more homework, which thus occupies more of their time, reducing the time available for screen-based activities.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, confirming previous findings [ 4 , 27 , 29 , 31 , 48 ], in this sample higher ST was found among girls indicating that they prefer certain sedentary activities in comparison to boys; Reading books, doing crafts or painting as well as listening to music or using the internet are more popular spare time activities among German girls, while German boys more often prefer sports or playing outside [ 52 ]. Further, also the association of ST with MVPA in this study potentially explains a part of the gender difference in sedentary behaviour.…”
Section: Discussionsupporting
confidence: 90%
“…However, no correlation of parental education level with ST was found in this study with a slightly younger sample. Because income and education are often investigated jointly in socio-economic status [ 27 , 31 ], evidence on these two single factors seems insufficient and partly inconsistent [ 31 ], wherefore no conclusion can be drawn yet. Although this study did not confirm this, in the current literature there is a tendency towards a positive association of school related ST and a negative association of screen-based ST with higher parental education [ 53 ], while income might be weakly negatively correlated to ST.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations